Strategic Management of Professional Service Firms Theory and Practice - Kaiser, Stephan; Ringlstetter, Max Josef; SpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
Managing strategies for professional service firms is an important and complex activity. The main issues in this book cover the core management principles for service firms in a comprehensive way. Based on current research findings it includes the management of service quality, knowledge and marketing as well as people, organizational and strategic issues. In understanding critical resources managers and partners will be able to effectively develop and exploit them. The book contains practical advice and offers a profound insight into the managerial excellence of service companies.
Part i: professional service firms -- 1. the world of professional service firms -- 2. the business of professional service firms -- 3. the subsectors of professional service firms -- part ii: management of strategic resources -- 1. quality management -- 2. knowledge management and innovation -- 3. marketing and relationship management -- part iii: management of professionals -- 1. human resource management in professional service firms -- 2. professional service firms as high performance work systems -- 3. work-life balance in professional service firms -- 4.the alumni network -- part iv: management of strategic development -- 1. strategic development of professional service firms -- 2. networking as a strategy for small and medium professional service firms -- 3. surviving crises - crisis management -- 4. archetype change towards management.
Electronic reproduction.
Keywords: Professional corporations -- Management; Strategic planning; Electronic books